2020
DOI: 10.1159/000512221
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Decreases in the Expression of Calcineurin and GABAA Receptors Induced by Early Maternal Separation Are Associated with Increased Anxiety-Like Behavior in Adult Male Rats

Abstract: <b><i>Introduction:</i></b> Early life stress is a well-described risk factor of anxiety disorders in adulthood. Dysfunction in GABA/glutamate receptors and their functional regulator, calcineurin, is linked to anxiety disorders. Here, we investigated the effect of early life stress, such as repeated maternal separation (MS; 3 h per day from postnatal day [P] 2 to 11), on changes in the expression of calcineurin as well as the ionotropic glutamatergic and GABAergic receptors including α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Studies have also shown that ELA reduces both allopregnanolone levels and GABA A receptor binding 92 , 93 , suggesting that this endogenous buffering mechanism may be disrupted after MSEW, although previous studies have not considered ELA-induced effects on these measures in the context of estrous stage. Our findings are consistent with the possibility that MSEW-induced increases in avoidance behavior during diestrus are the result of diminished conversion of progesterone to allopregnanolone.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that ELA reduces both allopregnanolone levels and GABA A receptor binding 92 , 93 , suggesting that this endogenous buffering mechanism may be disrupted after MSEW, although previous studies have not considered ELA-induced effects on these measures in the context of estrous stage. Our findings are consistent with the possibility that MSEW-induced increases in avoidance behavior during diestrus are the result of diminished conversion of progesterone to allopregnanolone.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that ELA reduces both allopregnanolone levels and GABA A receptor binding (Frye et al, 2006; Mahmoodkhani et al, 2020), suggesting that this endogenous buffering mechanism may be disrupted after MSEW, although previous studies have not considered ELA-induced effects on these measures in the context of estrous stage. Our findings are consistent with the possibility that ELA-induced increases in avoidance behavior during diestrus are the result of diminished conversion of progesterone to allopregnanolone.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that ELA reduces both allopregnanolone levels and GABA A receptor binding 82,83 , suggesting that this endogenous buffering mechanism may be disrupted after MSEW, although previous studies have not considered ELA-induced effects on these measures in the context of estrous stage. Our findings are consistent with the possibility that ELA-induced increases in avoidance behavior during diestrus are the result of diminished conversion of progesterone to allopregnanolone.…”
Section: Discussionmentioning
confidence: 99%